Affordability in the provision of water and sanitation services: Evolving strategies and imperatives to realise human rights - Brown, Colin; Heller, Léo (International Journal of Water Governance, 2017)
Affordability in access to drinking water and sanitation services (WSS) is an essential component for the realisation of the human rights to water and sanitation (HRtWS). The Sustainable Development Goals aim to provide adequate WSS to the remaining billions of people still left behind and explicitly recognise that water must be affordable to users in the variety of their particular conditions and needs. As one of the normative content under the human rights framework, affordability can be integrated into the broader principle of providing social equity and sustainable services to all people. Accessing WSS implies managing a wide range of costs—not all of them financial—that can differ in any given State or region. Indeed, difficulties are common in providing WSS in a way that reconciles affordability and economical sustainability, which generates tension in service provision. A particularly problematic aspect concerns applying mechanisms that successfully attain all people in society who require help while not offering undeserved assistance to people with comparatively lesser needs. In sum, affordability is attained through various efforts: a coordinated institutional structure, clear legal provisions (i.e. formally recognizing the HRtWS), contextually specific policy and plans, accountable regulatory mechanisms and efficiently organised service providers.